THE STRICTNESS OF CONDITIONS IN SOCIAL ASSISTANCE SYSTEMS: A COMPARISON OF LITHUANIA AND OTHER EUROPEAN COUNTRIES - Matulionytė, Rimgailė; Navickė, Jekaterina (Socialinė teorija, empirija, politika ir praktika, 2018)
This article proposes an index of conditionality in social assistance, which allows us to analyze and to compare the strictness of social assistance conditions in Lithuania and elsewhere in the EU. The proposed index combines three dimensions: strictness of the applied means-testing; conditions for participation in the labor market; limits on duration and amount of social assistance. Indicators characterizing these dimensions were collected using the MISSOC and EUROMOD databases. We estimate the index for 2016 and assess the strictness of the Lithuanian system of social assistance in the EU context. We also analyze the correlation between the index and indicators of poverty, social exclusion and income inequality. The results show considerable differences in the conditionality of social assistance across the EU. The Lithuanian system is very strict when compared to the other EU countries. Similar is true about the other Baltic countries. The strictness of social assistance conditions in Lithuania is higher than the EU average in all the analyzed dimensions. Means-testing for social assistance in Lithuania includes strict limits on property, income from work and other sources. There are also numerous conditions for job search, labor market participation, unpaid community work etc. Those not complying face strict sanctions. Lithuania applies the strictest limits on social assistance duration and amounts. It is the only country where in-cash payments can be discontinued after 60 months of receipt. Social assistance is withdrawn almost proportionally with additional income, i.e., at around a 90% rate. There is a lack of positive incentives for the working benefit recipients. It can also be concluded that the latest social assistance reform of 2012–2014 increased the strictness of the system of social assistance in Lithuania. Furthermore, the research has revealed that conditions limiting the duration and amount of social assistance are positively associated with the analyzed socioeconomic indicators. In countries with stricter limits on social assistance size and its shorter duration, the rates of poverty risk, social exclusion and income inequality are observed to be higher.